Agriculture and economic growth: Japan's experience - Okawa, Kazushi; Johnston, Bruce F.; Kaneda, Hiromitsu (Princeton, N.J. : Princeton University Press, 1970)
This book examine the contribution of various aspect of agricultural development and it's relation to economic growth in Japan
"The final version of a set of papers that were examined critically at the International Conference on Agriculture and Economic Development: a Symposium on Japan's Experience which was held in Tokyo, July 3-7, 1967."
Includes bibliographies.
oo 23/01/2019
Loans
Keywords: Agriculture; Japan